Os impactos da reestruturação organizacional de uma empresa multinacional de alta tecnologia na área de treinamento e desenvolvimento de call center:aplicação da teoria das configurações de Mintzberg - Carvalho, Silvia Helena Gomes de (2015)
A research study was conducted in the services sector of a high technology multinational company that underwent organizational changes in the training and development area, which offers support to various call center clients. Such changes required that the training team shift from reporting to the local Operational Management to the Global Training & Development area. The objective of this study is to contribute to the role of organizational design in the training area in the aforementioned sector. Based on Mintzberg's Five Configurations theory, we answered the following questions: what restructuring is the studied company implementing according to Henry Mintzberg's theory and what is the impact of this restructuring on the studied department from the viewpoint of the interviewees? We used the case study research methodology, which was conducted in Brazil with direct observation and field research, during which we conducted semi-structured interviews with the area's staff and clients to collect data. The study has shown that the training area was being restructured as an Operational Adhocracy, which is perceived positively by both the training staff and its clients. In order to assess the group's individual behaviors, two typologies were created based on the categorization of the collected data, which showed that the group's individuals had a strategic approach and focus on their professional development. Such results are consistent with Mintzberg's Adhocracy theory. The characteristics of an Adhocracy proved to be positive for a call center training area offering support to multiples clients, in that it leads the training team to think more strategically, to become more deeply engaged and autonomous, to communicate more effectively, and to benefit from flexible processes. Consequently, it brought positive results for the operations supported by the training team.